Genome-wide association study and genomic prediction for hessian fly resistance in ICARDA’s elite bread wheat genotypes - Imseg, Imane; Zakaria, EL Gataa; Karima, Samir; Boulamtat, Rachid; El Bouhssini, Mustapha; Tadesse, Wuletaw (Springer Verlag, 2025)
The Hessian fly, scientifically known as Mayetiola destructor (Say), is an agricultural pest that causes a substantial decrease in wheat productivity, especially in dry countries like Morocco, where it can decrease yields by about 32–36% during seasons of low rainfall. An essential method to reduce harm caused by this pest is to identify wheat genotypes that have natural resistance. The aim of this research was to pinpoint genomic regions, delineate marker-trait associations (MTAs), and identify candidate genes linked to Hessian fly resistance. We used 188 elite bread wheat genotypes obtained from the International Center for Agricultural Research in Dry Areas (ICARDA) for this study. The Hessian fly population utilized for screening was collected from the Chaouia Ouardigha region of Morocco and evaluated in a growth chamber maintained at precise conditions. Out of the 188 genotypes examined, 66 accessions showed high resistance to the Hessian fly. We used a mixed linear model (MLM) in our genome-wide association studies (GWAS) to discover 24 significant marker-trait associations (MTAs) linked to resistance to the Hessian fly (P < 0.001). The B sub-genome had the highest number of MTAs, with 14 markers related. The wsnp_BQ166999B_Ta_2_1 marker on chromosome 5B was notably significant, with a -Log10(p) value of 3.99, we also identified 18 potential candidate genes. This study successfully highlights wheat genotypes with high levels of HF resistance and notable SNP markers, offering valuable insights for upcoming breeding programs focused on wheat resilience.